Urgensi Penyesuaian Ketentuan Pidana Pada Undang-Undang Di Luar KUHP 2023 Dalam RUU Penyesuaian Pidana - Syafrina, Henin Dyah; Naura Tsurayya Hasnaa; Slamet Sudi Illahi; Bintang Pramadhani Hariadi Putra (DIKTUM: Jurnal Syariah dan Hukum, 2026)
Background: The enactment of the 2023 Indonesian Criminal Code has restructured the national penal system through a unified sentencing framework grounded in rehabilitative and restorative principles. However, the persistence of criminal provisions in numerous sectoral statutes creates normative fragmentation and structural disharmony within Indonesia's criminal law system. Aims: This article examines the phenomena of fragmentation and localization of criminal norms in the post-KUHP 2023 era through a fiqh anthropological perspective. Methodology: Using normative and conceptual legal approaches enriched by legal anthropology analysis, this study argues that the harmonization process embodied in the Sentencing Adjustment Bill is not merely a technical legislative alignment but represents a deeper negotiation between codified national norms and socio-cultural legal consciousness. Results: The abolition of mandatory minimum penalties and the realignment of fine categories illustrate the transition from rigid positivism toward contextualized penal policy. Implication: From a fiqh anthropological standpoint, harmonization must integrate principles of maqāṣid al-sharī'ah, 'urf, and substantive justice to prevent disconnection between state law and lived legal realities. Therefore, the transformation of criminal provisions outside the Criminal Code is not only a structural reform but also an epistemological shift in Indonesia's criminal legislative policy.